Lived experience of bereaved parents of young children : the role of spirituality and religion for coping with loss - Wu, Minyu (2016)
This paper aims to explore the lived experience of bereaved parents of young children and the supportive role of spirituality and religion in helping them cope with their loss. This study offers a new perspective into the subject as it focuses on the Asian context, incorporating the experiences of different religions. This is a qualitative research, adopting a descriptive phenomenological approach to capture lived experiences and to find common emerging themes in different religions. Four parents of different religions who were at least one and a half years into bereavement participated in this study. It was found that parents journey through three phases, “Pre-loss, Separation”, “Liminality, Segregation” and “Post-loss, Integration”. In Phase 1, there are seven themes related to religion and spirituality. Amongst the themes, religion provided strength and support while meaning making and acceptance helped parents come to terms with their children’s impending death. Phase 2 refers to the time that their children are at the brink of death. At this point, parents prepare themselves for their children’s final journey. Three different kinds of support, in the spiritual, bereavement and social aspects are most helpful to parents are this moment. In Phase 3, the four themes that emerged have religion and spirituality intertwined. They are mostly related to parents rebuilding their lives reintegrating back to their normal lives. Religion and spirituality was found to be helpful for bereaved parents. It is recommended that palliative care workers incorporate aspects of religion and spirituality when journeying with parents throughout the three phases.